Cardiac diseases in pregnancy and its feto-maternal outcome - Shah, Parul T.; Bhagat, Mohini A.; Patel, Rina V.; Yadav, Swati M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cardiac disease complicates 1-3% of all pregnancies. Of this Rheumatic heart disease constitute 74% and congenital heart disease 26%. Methods: A retrospective study of all patients with cardiac diseases delivered was conducted. A tabulated representation of the data was done. The various cardiac diseases were categorized according the severity, NYHA classification, type of pathology, the maternal and perinatal outcome was assessed, and the maternal mortality and perinatal mortality was recorded. Results: 84% patients belonged to age group 20-29 years. 8% were teen aged and 4% patients were elderly. 64% patients were either P0+0 or P0+1. 8% patients were P0+3 and 2% patient were P3+0. 74% patients had RHD. 26% had grade I, 40% had grade II, 20% patients had grade III and 14% had grade IV heart disease. The associated complications were anemia 46%, Respiratory tract infection 12%, pregnancy induced hypertension 2% and recurrent rheumatic fever 2%. 48% had normal vaginal delivery, 20% had forceps delivery and 32% had caesarean delivery. One mother died of heart failure. All patients of grade I (100%) had term delivery. 23.07% of grade I, 30% of grade II, 60% of grade III and 100% babies of grade IV mothers were of low birth weight (˂2.5 kg). Babies weighing ˂1.5 kg were seen in 5% grade II, 10% grade III and 42.85% mothers with grade IV disease. 2 of grade IV and each of grade I, II and III died. Conclusions: Feto-maternal outcome can be improved with close supervision of obstetrician and cardiologist throughout the pregnancy by antenatal care, early diagnosis and management.